Bill Clinton : United States president - Cole, Michael D. (Hillside, N.J. : Enslow Publishers, 1994)
Examines Clinton's personal and political life, from his childhood in Hope, Arkansas, through his tenure as Governor of Arkansas and his election and inauguration as the 42nd President of the United States.
William Jefferson Clinton -- Hope, Arkansas -- Growing up in a hurry -- A sixties education -- Yale, Hillary, and the first race -- The rising star -- Learning the hard way -- The comeback kid -- The national figure -- Wild race for the White House -- The biggest job in the world.
Includes bibliographical references (p. 104-110) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
8.0
5-8
Keywords: Clinton, Bill, -- 1946- -- Juvenile literature; Clinton, Bill, -- 1946-; Clinton, Bill, -- 1946-; Governors -- Arkansas -- Biography -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Governors -- Arkansas; Presidents; Governors -- Arkansas -- Biography; Presidents -- United States -- Biography